Training in Pesantren Manuscript Editing for Mahasantri in Lampung Province Through the Khastara Digital Portal of the National Library of Indonesia - M. Agus Mushodiq; Ikhwan Aziz Q; Adi Wijaya; Azzalya Itmi Nurekta; Hanafi Umar (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2026)
This study aims to analyze the implementation and impact of a training program on pesantren manuscript editing for mahasantri (university students from Islamic boarding schools) in Lampung Province through the Khastara digital portal of the National Library of Indonesia. This community service program employed a service-learning approach involving four stages: investigation, preparation, action, and reflection. Participants included 16 mahasantri from 10 pesantren in Lampung Province. Training was conducted through an intensive workshop at the Computer Laboratory of Universitas Ma'arif Lampung, utilizing the digital manuscript Kitab Safinatun Najah accessed via the Khastara portal. Results: reveal significant improvements in participants' philological and digital literacy competencies: 100% of participants successfully accessed and inventoried digital manuscripts through Khastara, 90% mastered standard Arabic-Latin transliteration, and the majority demonstrated proficiency in manuscript description, translation, and basic textual criticism. The program also established productive collaboration between universities, pesantren, and national institutions for preserving Indonesia's Islamic intellectual heritage. The service-learning-based manuscript editing training effectively enhances mahasantri's philological competencies while fostering academic responsibility and cultural preservation awareness. This integrated model offers a sustainable framework for digital philology education that can be adapted by other Islamic higher education institutions.